(untitled) (Libya Journal of Geographical Studies, 2025)
This study aimed to assess the condition of the vegetation cover in the Wadi An-Naqa basin following the devastating impact of Tropical Storm Daniel, which struck eastern Libya in September 2023. Extensive field surveys were conducted to evaluate the damage to the region. Soil erosion was estimated at a staggering 16 million tons per day, accompanied by the loss of approximately 29 km² (31%) of vegetation cover, as determined by Normalized Difference Vegetation Index (NDVI) analysis. Before the storm, the vegetation cover spanned 91 km², shrinking to 63 km² in its aftermath. Notable plant species such as Myrtus communis, Olea europaea, Juniperus phoenicea, and Nerium oleander were severely affected. Remarkably, some uprooted trees were estimated to be over 500 years old, indicating an unprecedented event in the region’s recent history. Additionally, the study revealed the emergence of toxic plant species, including Datura and Ricinus communis, which were previously absent from the area’s vegetation.